Exploring the Role of Improvisation and Implementation Challenges in Science Teaching: A Standard-Based Curriculum Study - Charity Esenam Anor; Daniel Morrison; Zaaria Sibaweihi (Integrated Science Education Journal, 2026)
Purpose of the study: Standards-based curriculum reforms emphasise competency development and learner-centered pedagogy, yet implementation in resource-constrained contexts remains underexplored. While research has documented general curriculum implementation challenges, limited empirical evidence exists on specific challenges in science teaching and how teachers employ improvisation to bridge resource gaps in competency-based science education. Methodology: A qualitative case study design was employed involving five science teachers purposively selected from five government basic schools in Ghana. Data were collected through semi-structured interviews, audio-recorded and transcribed. Thematic analysis identified patterns and themes. The interview protocol was adapted from established curriculum implementation instruments and validated through expert review with trustworthiness ensured. Main Findings: Four major challenges emerged as inadequate teacher training in competency-based pedagogy, insufficient instructional resources and laboratory equipment, difficulties implementing authentic assessment, and challenges adapting curriculum content to local contexts. Teachers employed systematic improvisation using locally available materials, which enhanced student engagement, facilitated conceptual understanding of abstract concepts, and aligned with learner-centered objectives. However, improvisation was constrained by time limitations, lack of institutional support, and absence of formal training in material adaptation. Novelty/Originality of this study: This study provides empirical evidence that teacher improvisation constitutes a deliberate pedagogical strategy rather than a compensatory response to resource scarcity, as systematically improvised materials significantly enhance engagement and conceptual understanding. The key implication calls for a policy shift prioritising formal improvisation training, institutional time allocation for material adaptation, and professional recognition of improvisation as valid pedagogy.